The Implementation of E-Commerce Consumer Option Rights (Khiyar) in Realizing Transaction Justice: A Study of Maqasid Al-Shariah - Abdi Wijaya,; Idrus, Achmad Musyahid; Maulidah, Tahani Asri; Asti, Mulham Jaki; Nurjannah, Nurjannah (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
This article aims to reveal the optimization of option rights in realizing or stopping e-commerce transactions to achieve justice due to several problems in e-commerce transactions, including no meeting of two people who transact and no goods at that time. The results of the study reveal that the component of option rights (khiyar) focuses on an option due to damage/defect, where the damage can harm or oppress the parties, and the right to vote is a preventive alternative so that the parties feel comfortable and justice is realized in every transaction. Likewise, in the maqashid al sharia analysis, option rights (khiyar) have a very strategic role in maintaining the interests, transparency, benefit, and willingness of both parties to conduct transactions and protect them from harm and loss for all parties. This shows concern for justice in transactions as an effort for the common good to protect the rights of the parties. Strengthening regulations through laws and regulations needs to be carried out as a preventive effort to prevent acts of bad faith by one of the parties to provide a sense of security in transactions between the parties.